Pengembangan Website Profil dan Sistem PPDB Online TK Al-Mumtaza sebagai Media Informasi dan Promosi Sekolah - Roihan Wira Assidiqi; Rizka Yulianti; Murni; Andri Nofiar. Am; Tri Handayani; Supriati (Jurnal Inovasi Pengabdian Masyarakat, 2026)
This community service program aims to address the digital and administrative limitations faced by TK Al-Mumtaza in Senggoro, Bengkalis, by developing a web-based school profile and an online student admission system (PPDB). Previously, the school lacked a digital footprint, and the registration process was conducted manually, leading to inefficiencies and scattered data. To solve these issues, the project applied the diffusion of technology through the development of a website using the Laravel framework and Tailwind CSS, executed via a Project-Based Learning (PjBL) approach. The implementation method included requirements analysis, system development, testing, deployment, and mentoring. The result of this service was a fully functional and publicly accessible website that successfully centralized the registration data into a secure database. The implementation significantly improved the efficiency of the admission process, allowing parents to register online from home, and broadened the school's promotional reach. In conclusion, the integration of a digital profile and automated PPDB system effectively modernized TK Al-Mumtaza's administrative workflow and information dissemination.